Analisis Struktur, Pertumbuhan, dan Ketimpangan Ekonomi Wilayah di Provinsi Jawa Tengah (Indo-MathEdu Intellectuals Journal, 2026)
Regional economic development requires information on economic structure, sectoral advantages, sources of growth, and regional disparities as a basis for policy formulation. This study aims to analyze the economic structure, identify basic sectors and competitive advantages, and evaluate regional development disparities in Central Java Province for the 2021–2025 period. The study uses a quantitative approach with secondary data on Gross Regional Domestic Product (GRDP) at constant prices in 2010 published by the Central Statistics Agency. Data analysis was conducted descriptively using the Location Quotient (LQ), classic Shift Share, and the Williamson Index. The results show that Central Java's economic structure is still dominated by the Manufacturing Industry and Agriculture sectors. The LQ analysis identified six basic sectors: Manufacturing Industry, Agriculture, Construction, Trade, Accommodation and Food and Beverage Provision, and Educational Services. The Shift Share analysis shows that the Manufacturing Industry has the highest negative shift differential, while the Transportation and Warehousing, Construction, and Educational Services sectors have competitive advantages. The Williamson Index ranges from 0.63 to 0.69, with an average of 0.6548, indicating that regional development inequality remains high. This finding provides the basis for policy development to strengthen the competitiveness of basic sectors and promote equitable development across regions in Central Java Province.